Tumor necrosis factor‐alpha inhibitors and risk of non‐Hodgkin lymphoma in a cohort of adults with rheumatologic conditions. Issue 5 (16th April 2018) - Calip, Gregory S.; Patel, Pritesh R.; Adimadhyam, Sruthi; Xing, Shan; Wu, Zhaoju; Sweiss, Karen; Schumock, Glen T.; Lee, Todd A.; Chiu, Brian C.‐H.
Abstract : Based on limited evidence, the U.S. Food and Drug Administration (FDA) issued a black box warning for the use of tumor necrosis factor‐alpha inhibitors (TNFIs) and risk of non‐Hodgkin lymphoma (NHL). Our objective was to determine the risk of NHL associated with TNFI use by duration and type of anti‐TNF agent. We performed a nested case‐control study within a retrospective cohort of adults with rheumatologic conditions from a U.S. commercial health insurance database between 2009 and 2015. Use of TNFIs (infliximab, adalimumab, etanercept, golimumab and certolizumab pegol) and conventional‐synthetic disease‐modifying antirheumatic drugs (csDMARDs) was identified, and conditional logistic regression models were used to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI) for risk of NHL. From a retrospective cohort of 55, 446 adult patients, 101 NHL cases and 984 controls matched on age, gender and rheumatologic indication were included. Compared to controls, NHL cases had greater TNFI use (33% vs . 20%) but were similar in csDMARD use (70% vs . 71%). TNFI ever‐use was associated with nearly two‐fold increased risk of NHL (OR = 1.93; 95% CI: 1.16–3.20) with suggestion of increasing risk with duration (P‐trend = 0.05). TNF fusion protein (etanercept) was associated with increased NHL risk (OR = 2.73; 95% CI: 1.40–5.33), whereas risk with anti‐TNF monoclonal antibodies was not statistically significant (OR = 1.77; 95% CI: 0.87–3.58). In sensitivity analyses evaluating confounding by rheumatologic disease severity, channeling bias was not likely to account for our results. Our findings support the FDA black box warning for NHL. Continued surveillance and awareness of this rare but serious adverse outcome are warranted with new TNFIs and biosimilar products forthcoming. Abstract : What's new? TNF inhibitors (TNFIs) are used to treat autoimmune and inflammatory disorders. However, the U.S. FDA has issued a black‐box warning for these drugs, as they may increase the risk of non‐Hodgkin lymphoma (NHL). In this large follow‐up study, the authors found that NHL risk increases with increased duration of TNFI use, and increased more with some TNFIs than with others. Continued awareness of this rare but serious adverse outcome is thus warranted, with new agents and biosimilar products entering the market or in the pipeline.